Ground Water Quality of Gandhinagar Taluka, Gujarat, India - Mayur C. Shah; Prateek G. Shilpkar; Pradip B. Acharya (E-Journal of Chemistry)
Present communication deals with study of physico-chemical parameters such as pH, electrical conductivity (EC), total dissolved solids (TDS), total alkalinity (TA), calcium hardness (CaH), magnesium hardness (MgH), total hardness (TH), chloride (Cl-), fluoride (F-), sodium (Na+), potassium (K+), dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD) and sulphate (SO42-) of water samples of bore wells of forty villages of Gandhinagar taluka of Gujarat state,India. The experimental values of water samples were compared with standard values given by World Health Organization (WHO) and United State Salinity Laboratory for drinking and irrigation purposes respectively. Water Quality Index (WQI) was also calculated to know the over all quality of water samples. The statistical analysis like mean, standard deviation (SD), coefficient of variance (% CV), analysis of variance (ANOVA), t-test, coefficient of correlation (r) and regression analysis of obtained data were carried out. The results show that the quality of water is poor and quite good for drinking and irrigation purposes respectively. The variance was found significant at 1% level of significance in case of sodium and potassium content and at 5% in case of total alkalinity and dissolved oxygen among the four regions (North, South, East and West) of Gandhinagar taluka. The linear relation also established for each pair of water quality parameters of studied water samples.